Single-mother poverty: How much do educational differences in single motherhood matter? - Juho Härkönen (Luxembourg Income Study (LIS), 2017)
Recent research on family demography and social inequality has paid attention to the divergence in family structures by education. This research has shown how single motherhood prevalence has increased markedly among the low educated, while remaining stable at relatively low levels among the highly educated. Because single motherhood is associated with a host of economic disadvantages, these trends can amplify social inequalities. In this chapter, I use data for 15 countries from the Luxembourg Income Study (LIS) Database to analyze whether educational differences in single motherhood increase single-mother poverty, and the poverty gap between single-mother and coupled-parent households. Single-mother poverty rates and the single-mother poverty gap would both be lower in the absence of educational differences in single motherhood. However, the importance of educational differences in single motherhood is conditional on how high single-mother poverty rates are in different educational groups; educational differences in single motherhood matter less when educational differences in single-mother poverty are smaller. I conclude that social policies should aim to reduce poverty among all families. As a side-effect, educational differences in single motherhood would be less important in shaping social inequality.
Keywords: 330